Eläkevarat ja riskien jako työeläkejärjestelmässä; Pension Funds and Risk-sharing in the Finnish Earnings-related Pension System - Jukka Lassila; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2019)
– We study the use of pension funds in the Finnish earnings-related pension system with the aim of smoothing contributions over time under demographic and economic risks. Smoothing is affected by the revisions in long-term forecasts and is thus imperfect. As a partially funded defined-benefit system, demographic risks and asset yield risks directly affect the contributions. In a general equilibrium setup, these risks also affect wages and thus pension benefits and replacement rates. We also consider alternative benefit rules where risks are transferred more to the pensioners.
Keywords: E17; H55; 330; Pensions; Funding; Contribution smoothing; Risks; Generational fairness